Frequency and phenotypic implications of mitochondrial DNA mutations in human squamous cell cancers of the head and neck - Zhou, Shaoyu (National Academy of Sciences, 2007)
Mitochondrial genomic mutations are found in a variety of human cancers; however, the frequency of mitochondrial DNA (mtDNA) mutations in coding regions remains poorly defined, and the functional effects of mitochondrial mutations found in primary human cancers are not well described. Using MitoChip, we sequenced the whole mitochondrial genome in 83 head and neck squamous cell carcinomas. Forty-one of 83 (49%) tumors contained mtDNA mutations. Mutations occurred within noncoding (D-loop) and coding regions. A nonrandom distribution of mutations was found throughout the mitochondrial enzyme complex components. Sequencing of margins with dysplasia demonstrated an identical nonconservative mitochondrial mutation (A76T in ND4L) as the tumor, suggesting a role of mtDNA mutation in tumor progression. Analysis of p53 status showed that mtDNA mutations correlated positively with p53 mutations (P < 0.002). To characterize biological function of the mtDNA mutations, we cloned NADH dehydrogenase subunit 2 (ND2) mutants based on primary tumor mutations. Expression of the nuclear-transcribed, mitochondrial-targeted ND2 mutants resulted in increased anchorage-dependent and -independent growth, which was accompanied by increased reactive oxygen species production and an aerobic glycolytic metabolic phenotype with hypoxia-inducible factor (HIF)-1α induction that is reversible by ascorbate. Cancer-specific mitochondrial mutations may contribute to development of a malignant phenotype by direct genotoxic effects from increased reactive oxygen species production as well as induction of aerobic glycolysis and growth promotion.